2020
DOI: 10.1200/jco.2020.38.15_suppl.9011
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab plus stereotactic ablative therapy for medically inoperable patients with early-stage non-small cell lung cancer.

Abstract: 9011 Background: Stereotactic ablative radiation therapy (SABR) is the standard-of-care for medically inoperable, early stage non-small cell lung cancer (NSCLC), but regional and distant failures remain problematic. Based on our in vivo data showing synergy between radiation and immune checkpoint inhibitors (ICI) and the known efficacy and mild toxicity profile of ICI in NSCLC, we conducted a phase I study to determine the maximum tolerated dose of neoadjuvant, concurrent, and adjuvant atezolizumab with SABR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Notably, the substantially improved PFS was associated with an increased TIL score, the presence of an immune-related adverse event, and relative T cell activation status. Moreover, a phase I study conducted by Kelly et al explored the efficacy and safety of atezolizumab plus SBRT for patients with medically inoperable early-stage NSCLC [ 69 ]. The preliminary results updated in the 2020 ASCO indicated that the combination treatment was a feasible choice with no significant additional toxicities.…”
Section: Current Advances In Sbrt and Pd-1/pd-l1 Inhibitors For Nsclcmentioning
confidence: 99%
“…Notably, the substantially improved PFS was associated with an increased TIL score, the presence of an immune-related adverse event, and relative T cell activation status. Moreover, a phase I study conducted by Kelly et al explored the efficacy and safety of atezolizumab plus SBRT for patients with medically inoperable early-stage NSCLC [ 69 ]. The preliminary results updated in the 2020 ASCO indicated that the combination treatment was a feasible choice with no significant additional toxicities.…”
Section: Current Advances In Sbrt and Pd-1/pd-l1 Inhibitors For Nsclcmentioning
confidence: 99%
“…A phase I study conducted by Kelly et al explored the efficacy and safety of atezolizumab plus stereotactic ablative radiation therapy (SBRT) for medically inoperable patients with early-stage NSCLC. The preliminary results showed that the combined treatment was a feasible option without obvious additional toxicity [ 14 ]. Moreover, the results of phase II prospective trial in patients with metastatic NSCLC reported that the combination of SBRT with concurrent pembrolizumab led to increased PFS, with a systemic response rate of 9.52% and a DCR of 57.14% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of ongoing phase III studies investigating this combination in the definitive setting will likely be informative. Currently, PACIFIC-4 (NCT03833154) and SWOG/NRG S1914 (NCT04214262), both of which randomize patients with early-stage NSCLC with high-risk features to treatment with SBRT with or without consolidative ICB, are currently enrolling (119,120). Notably, patients treated on the experimental arms of these studies receive radiation therapy with biologically effective doses (BEDs) in excess of 100 Gy in combination with ICB and as a result, the outcomes of these trials will likely provide additional valuable information on the safety of combining ablative doses of radiation with ICB.…”
Section: Safety Of Icb With Sbrtmentioning
confidence: 99%